2017
DOI: 10.1111/ajd.12644
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal epidermal naevi as a feature of systematised epidermal naevus syndrome

Abstract: Systematised epidermal naevi are hamartomas developing from neural ectoderm that can be quite extensive, typically with involvement of the face, neck, scalp, arms, legs and trunk. Involvement of the gastrointestinal tract is rare. We report on a 38-year-old Caucasian woman with systematised epidermal naevus syndrome who presented with previously undescribed involvement of the oesophagus, as well as the right side of her scalp, forehead, cheeks, chin, oral mucosa, neck, arms and trunk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This multisystemic syndrome mostly involves the brain, head and neck area, arms, and trunk. Oyesanya et al reported the first case of verrucous epidermal naevi of the esophagus [ 46 ].…”
Section: Mesenchymal Hamartomasmentioning
confidence: 99%
“…This multisystemic syndrome mostly involves the brain, head and neck area, arms, and trunk. Oyesanya et al reported the first case of verrucous epidermal naevi of the esophagus [ 46 ].…”
Section: Mesenchymal Hamartomasmentioning
confidence: 99%
“…ENS is defined as epidermal nevus with multisystem involvement such as central nervous system, skeleton, and in some cases, the gastrointestinal tract. 1,2 Presence of keratinocytic nevus and nevus spilus among with other abnormalities has been reported in some epidermal nevus syndromes. [1][2][3] Here a case of 5-year-old girl with keratinocytic epidermal nevus, nevus spilus and hemi-hypertrohpy which is not consistent with any of the reported ENSs, showing a rare coexistence, is presented.…”
mentioning
confidence: 97%